Modified Constitutive Model and Practical Calibration Method for Constructional 7075-T6 Aluminum Alloy - Yishu Zhang; Lin Zhao; Zhenggang Cao; Bizhao Wu (Buildings, 2025)
Recently, high-strength 7075-T6 aluminum alloy has demonstrated promising application prospects in large-span spatial structures given its exceptional mechanical properties. However, the classical Ramberg–Osgood (R–O) constitutive model cannot accurately predict the mechanical behavior of 7075-T6 aluminum alloy in the large-strain stage, compromising the structural reliability of designs. Herein, the full-range stress–strain curves of 7075-T6 aluminum alloy were investigated through tensile tests. Mechanical property indices were obtained, and the classical R–O model was calibrated for 7075-T6 aluminum alloy. Furthermore, an improved R–O model based on piecewise functions was proposed to address the significant prediction errors under large-strain conditions (ε > 0.015). Compared with the classical R–O model, the modified model exhibited a reduction of over 75% in stress–strain curve deviation. Moreover, an approximate value method only based on nonproportional extension strength and elastic modulus was proposed for the calibration of the modified model, considerably enhancing the engineering practicality of the modified constitutive model.